Influence of Work Motivation, Job Satisfaction and Work Discipline on Employee Performance at PT. Truba Jaga Cita - Hustia, Anggreany; Hendro, Omar; Herlangga, Teja (LPPM Universitas Bina Bangsa, 2021)
This study aims to determine the influence of work motivation, job satisfaction and work discipline on employee performance at PT. Truba Jaga Cita. The study's population was 195 employees and a sample of 131 people was determined using the slovin formula. The data used is primary data using the results of the disseminated questionnaire. The analytical techniques used in this study are multiple linear regression analysis, hypothesis test, and determination test The results of multiple linear regression analysis and hypothesis test through F test say that there is an influence of work motivation, job satisfaction and work discipline on employee performance at PT. Truba Jaga Cita. Hypothetical test results through t test say that first, there is a significant influence of work motivation on employee performance at PT. Truba Jaga Cita. Second, there is a significant influence of job satisfaction on employee performance at PT. Truba Jaga Cita. Third, there is a significant influence of work discipline on employee performance at PT. Truba Jaga Cita